Prevention of diseases associated with obesity in adult women - Xiomara Columbié-Matos; Santiago Savigne-Betancourt (Universidad de Guantánamo, 2013)
The present work aims to develop a game system for the prevention of diseases associated with obesity in adults in Tortuguilla community from Saint Anthony of South Municipality. The practical contribution of the research lies in inserting a novel gaming system for obese adults which are aimed at prevention of diseases associated with obesity in adult games developed system is an important tool for professionals serving the community work aimed at preventing the diseases that are associated with obesity in adults.